GENE-DOSAGE EFFECTS ON FITNESS IN RECENT ADAPTIVE DUPLICATIONS: ace-1 IN THE MOSQUITO CULEX PIPIENS. (1st July 2014) - Labbé, Pierrick; Milesi, Pascal; Yébakima, André; Pasteur, Nicole; Weill, Mylène; Lenormand, Thomas
Abstract: Gene duplications have long been advocated to contribute to the evolution of new functions. The role of selection in their early spread is more controversial. Unless duplications are favored for a direct benefit of increased expression, they are likely detrimental. In this article, we investigated the case of duplications favored because they combine already functionally divergent alleles. Their gene-dosage/fitness relations are poorly known because selection may operate on both overall expression and duplicates relative dosage. Using the well-documented case of Culex pipiens resistance to insecticides, we compared strains with various ace-1 allele combinations, including two duplicated alleles carrying both susceptible and resistant copies. The overall protein activity was nearly additive, but, surprisingly, fitness correlated better with the relative proportion of susceptible and resistant copies rather than any absolute measure of activity. Gene dosage is thus crucial, duplications stabilizing a "heterozygote" phenotype. It corroborates the view that these were favored because they fix a permanent heterosis, thereby solving the irreducible trade-off between resistance and synaptic transmission. Moreover, we showed that the contrasted successes of the two duplicated alleles in natural populations depend on genetic changes unrelated to ace-1, confirming the probable implication of recessive sublethal mutations linked to structural rearrangements in some duplications.